From Complaints to Satisfaction: Transforming PDAM Customer Complaints Services in the Digital Era - Sulmiah, Sulmiah (Universitas Negeri Makassar, 2025)
The digitalization era demands transformation in customer complaint handling for public service companies, including PDAMs that face challenges in responsiveness and service quality. This study aims to analyze customer complaint handling strategies at PDAM Tirta Danau Tempe in Wajo Regency based on Fandy Tjiptono's service quality dimensions. Using a qualitative approach with in-depth interviews and SWOT analysis, the research involved PDAM staff and customers as informants. Data were analyzed using the Miles-Huberman interactive model to identify complaint handling strategies through four indicators: empathy toward customers, handling speed, fairness in problem-solving, and ease of communication access. Results show that PDAM has implemented an integrated digital system for payments and complaints that is superior to other PDAMs, but still faces challenges in responsiveness, unstable water quality, and infrastructure limitations. The findings contribute to the literature by identifying a progressive digitalization model and confirming the need for a holistic approach in digital transformation of public services. Future research is recommended to use mixed-methods for more robust statistical validity and comparative studies across PDAMs